A Study on Commercial Activities in a readymade garments; understanding LC & shipment procedure to export goods of Aboni Knitwear Limited. - Debnath, Palash Kumar (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.